Fabrication and properties of PLA/β-TCP scaffolds using liquid crystal display (LCD) photocuring 3D printing for bone tissue engineering - Wang, Boqun; Ye, Xiangling; Chen, Guocai; Zhang, Yongqiang; Zeng, Zhikui; Liu, Cansen; Tan, Zhichao; Jie, Xiaohua (Frontiers in Bioengineering and Biotechnology, 2024)
Bone defects remain a thorny challenge that clinicians have to face. At present,scaffolds prepared by 3D printing are increasingly used in the field of bone tissue repair.Polylactic acid (PLA) has good thermoplasticity, processability, biocompatibility, and biodegradability, but the PLA is brittle and has poor osteogenic performance, which limits its application in bone tissue repair fields.Beta-tricalcium phosphate (β-TCP) has good mechanical properties and osteogenic induction properties,which can make up for the drawbacks of PLA. In this study, photocurable bio-PLA was used as raw material to prepare PLA/β-TCP slurries with different β-TCP contents and the β-TCP content increases, the rheological properties of PLA/β-TCP slurry exhibit non-Newtonian fluid properties. The PLA/β-TCP scaffold prepared using liquid crystal display (LCD) lightcuring 3D printing technology (β-TCP dosage is 0%, 10%, 20%, 30%, 35% of PLA dosage respectively). SEM results show that all scaffolds had a three-dimensional network structure, and as the amount of β-TCP increases, more β-TCP particles adhere to the surface of the scaffold and the surface becomes rougher. The compressive strength test results showed that the compressive strength of the PLA/β-TCP scaffold showed a trend of first increasing and then decreasing with the increase of β-TCP dosage, and reached the maximum value of 51.4 MPa when the β-TCP dosage was 10%, which was compatible with the compressive strength of natural bone. The results of the scaffolds degradation rate curve show that as time increases, the degradation rate of the scaffolds gradually increases, and the pH value of the stent becomes alkaline during the degradation process. In addition, we studied the biocompatibility and osteogenic properties of PLA/10%β-TCP scaffolds in vitro. Live/dead staining assay and hemocompatibility assay demonstrated that the prepared PLA/β-TCP scaffold had good biocompatibility. CCK-8 assay showed that the PLA/β-TCP group promotes cell proliferation.Moreover, ALP staining assay, ALP activity, Alizarin red stained, RT-qPCR and Immunofluorescence staining show that the prepared PLA/β-TCP scaffold exhibited a solid ability to promote the osteogenic differentiation of MC3T3-E1 cells in vitro.Therefore, 3D printed LCD photocuring PLA/β-TCP scaffolds can undoubtedly improve surface bioactivity and lead to better osteogenesis,which may provide a unique strategy for developing bioactive implants in orthopedic applications.